VITALITE Zambia Ltd : the intersection of solar energy technology and mobile money in Zambia (case A) - Perumal, Vimendree, (SAGE Business Cases., 2018)
Case A finds the Zambian energy startup VITALITE Ltd in April 2015, months after launching their first viable product pay-as-you-go solar home system (PAYGO SHS). The case follows the founders and their teammates as they consider an expansion strategy that addresses issues around their payment and distribution models. Ultimately, as a social enterprise with a mission to provide energy to rural households at the "bottom of the pyramid" (BoP), VITALITE must find a way to align their distribution and payment strategy with their marketing strategy. To do this, VITALITE explores various expansion approaches, including the expansion of their geographic footprint and internal infrastructure; integration of a cashless payment option via a mobile money platform; and formation of a distribution network through agricultural dealers in rural areas. In this case, these common challenges of startup business development are compounded by the emerging market context in Zambia. VITALITE must strategise within some specific constraints, including the geographic dispersion of the population, limited financial inclusion and literacy, and low rates of mobile money adoption and usage. The case concludes with the VITALITE team still debating the merits of their different options, leaving students to perform their own analysis and make proposals for the way forward.